Flexural analysis and design of stainless steel reinforced concrete beams. (1st November 2019) - Rabi, Musab; Cashell, K.A.; Shamass, R.
Highlights: Analysis of stainless steel reinforced concrete beams. A new design approach, based on the Continuous Strength Method, is presented and validated. A FE model is developed and validation and then used for further analysis. New design approach exploits the distinctive strain hardening properties of stainless steel. Abstract: The use of stainless steel reinforcement in concrete structures has increased in recent years, particularly in applications where corrosion and chemical resistance is desirable such as bridges, retaining walls and tunnels. Stainless steel has a wide range of attractive properties including excellent mechanical strength, fire resistance, durability and also a long life-cycle compared with carbon steel. However, it is also has a higher initial cost, and therefore needs to be used carefully and efficiently. The existing material models provided for the structural analysis of reinforced concrete members in current design standards, such as Eurocode 2, are not appropriate for stainless steel reinforced concrete and lead to overly conservative (or indeed unconservative in some cases) predictions of the section capacity. Generally, there is a lack of data in the public domain regarding the behaviour of concrete beams reinforced with stainless steel, mainly owing to this being a relatively new and novel topic. In this context, the current paper provides a detailed background of the existing information on stainless steel reinforced concrete, as well a discussion on the potential advantages and challenges. Then, attention is given to analysing the behaviour of stainless steel reinforced concrete beams by developing the Continuous Strength Method to predict the bending moment capacity. A finite element model has been develop in order to further assess the performance, and this is also used to conduct a parametric study of the most influential properties. It is concluded that the proposed analytical models provides a reliable solution for predicting the capacity of concrete beams reinforced with stainless steel.